Organogel electrolyte for high-loading silicon batteries. Issue 21 (10th May 2016) - Cho, Yoon-Gyo; Park, Hyungmin; Lee, Jung-In; Hwang, Chihyun; Jeon, Yuju; Park, Soojin; Song, Hyun-Kon
Abstract : A cyanoresin organogel electrolyte, characterized by in situ gelation with no initiators or crosslinkers, was used for high-loading silicon batteries of 1.3 mgSi cm −2 (equivalent to 3.3 mA h cm −2 ). Abstract : A cyanoresin organogel electrolyte, characterized by in situ gelation with no initiators or crosslinkers, was used for high-loading silicon batteries of 1.3 mgSi cm −2 (equivalent to 3.3 mA h cm −2 ). The organogel provided additional cohesion between the silicon particles and maintained electrode integrity even after pulverization, completely suppressing severe crack development and serious electrode thickness changes observed in liquid electrolytes. The capacity retention upon cycling was significantly improved in the organogel when compared with its liquid counterpart.